A facile fabrication of copper particle-decorated novel graphene flower composites for enhanced detecting of nitrite. Issue 4 (21st February 2015) - Wang, Huiwen; Wang, Caiqin; Yang, Beibei; Zhai, Chunyang; Bin, Duan; Zhang, Ke; Yang, Ping; Du, Yukou
<x xml:space="preserve">Abstract</x> A novel 3D porous flower-like reduced graphene oxide (f-RGO) was explored as the support material for the Cu particles on glassy carbon electrode (Cu/f-RGO/GCE) for detecting nitrite.